2014
DOI: 10.1016/j.bbamcr.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation and deimination of proteins: Two epigenetic modifications involved in Giardia encystation

Abstract: SUMOylation, a posttranslational modification of proteins, has been recently described as vital in eukaryotic cells. In a previous work, we analyzed the role of SUMO protein and the genes encoding the putative enzymes of the SUMOylation pathway in the parasite Giardia lamblia. Although we observed several SUMOylated proteins, only the enzyme Arginine Deiminase (ADI) was confirmed as a SUMOylated substrate. ADI is involved in the survival of the parasite and, besides its role in ATP production, it also catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Cannabinoids have previously been linked to inhibition of parasite invasion and immunosuppression of trypanosomiasis (Nok et al, 1994; Croxford et al, 2005) as well as acting as anti-helmitics (Roulette et al, 2016), but their effects on Giardia have hitherto not been investigated. Hovewer, GiADI has PAD activity (Touz et al, 2008; Vranych et al, 2014). For example citrullination of the antigenic Variable Surface Proteins (VSPs) through arginine residues of its cytoplasmic tail results in lower antigenic switch, interfering in trophozoite fitness due to cytotoxic antibody activity (Touz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids have previously been linked to inhibition of parasite invasion and immunosuppression of trypanosomiasis (Nok et al, 1994; Croxford et al, 2005) as well as acting as anti-helmitics (Roulette et al, 2016), but their effects on Giardia have hitherto not been investigated. Hovewer, GiADI has PAD activity (Touz et al, 2008; Vranych et al, 2014). For example citrullination of the antigenic Variable Surface Proteins (VSPs) through arginine residues of its cytoplasmic tail results in lower antigenic switch, interfering in trophozoite fitness due to cytotoxic antibody activity (Touz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Gl SUMO-deficient G. lamblia trophozoites displayed decreased proliferative ability and cell cycle arrest at G1/S phase, which resembles the effects of SUMO knockdown in trypanosomes [ 93 ]. It was also reported that Gl SUMO regulates the ability of G. lamblia trophozoites to transform into dormant cysts through modification of the parasite’s substrate arginine deiminase (ADI) [ 94 ]. SUMOylation of ADI on Lys101 promotes its localisation to the nucleus and leads to downregulation of cyst wall proteins (CWPs) expression, a necessary step for allowing the encystation process to complete.…”
Section: Sumo: Wrestling With Stress and Morementioning
confidence: 99%
“…SUMOylation of ADI on Lys101 promotes its localisation to the nucleus and leads to downregulation of cyst wall proteins (CWPs) expression, a necessary step for allowing the encystation process to complete. A potential mechanism of ADI-mediated CWP repression is the deimination of histones at the promoters of cwp genes, an epigenetic modification that may be conferred through the catalytic activity of ADI in the nucleus [ 94 , 95 ]. Although only 28 proteins were identified as potential substrates by means of mass spectrometry [ 93 ], the functional evidence discussed above suggests that Gl SUMO is instrumental in many diverse and essential processes to G. lamblia development, including cell cycle progression, cell shape control, adhesive disk formation, and encystation.…”
Section: Sumo: Wrestling With Stress and Morementioning
confidence: 99%
“…Western blot analysis of whole cell extracts with a monoclonal antibody against Giardia SUMO (mAb13C5) revealed that many proteins (from 50 to 120 kDa) are SUMOylated in trophozoites. Among them, arginine deiminase (ADI) was confirmed to be modified by SUMO at Lys 101 and Lys 387 and to be involved in cyst differentiation (Touz et al 2008;Vranych et al 2014). In this work, by obtaining a lineage of the parasite knocked down for SUMO we extend the functional analysis of the SUMOylation system in Giardia.…”
mentioning
confidence: 97%
“…; Vranych et al. ). In this work, by obtaining a lineage of the parasite knocked down for SUMO we extend the functional analysis of the SUMOylation system in Giardia .…”
mentioning
confidence: 97%